2003
DOI: 10.1046/j.1440-1819.2003.01093.x
|View full text |Cite
|
Sign up to set email alerts
|

Nightmares and dissociative experiences: The key role of childhood traumatic events

Abstract: In order to examine the co-occurrence of nightmares with dissociative experiences in the adolescent population and to demonstrate the impact of childhood traumatic events in this association, 292 undergraduate students were interviewed for childhood traumatic events. The Van Dream Anxiety Scale (VDAS) and Dissociative Experiences Scale (DES) were also administered to the subjects. For nightmares a 7.5% prevalence of 'often' and a 58.2% prevalence of 'sometimes' was found for college students. Nightmare prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
81
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(97 citation statements)
references
References 27 publications
14
81
2
Order By: Relevance
“…In clinics, the frequent nightmares are prevalent in 16.7% patients with schizophrenia [8], 17.5% depression [8,9], 25% substance or alcohol abuse [10,11], 49% borderline personality disorder [12,13], 57% dissociative disorder [14,15], and 90% post-traumatic stress disorder (PTSD) [16]. Moreover, the frequent nightmares happen in anxiety and bipolar disorders [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In clinics, the frequent nightmares are prevalent in 16.7% patients with schizophrenia [8], 17.5% depression [8,9], 25% substance or alcohol abuse [10,11], 49% borderline personality disorder [12,13], 57% dissociative disorder [14,15], and 90% post-traumatic stress disorder (PTSD) [16]. Moreover, the frequent nightmares happen in anxiety and bipolar disorders [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…It reported that depressive and dissociative Disorders are frequently observed together [5]. In some patients with dissociative amnesia, depression symptoms can accompany [6].…”
Section: Discussionmentioning
confidence: 99%
“…In most of the patients with parasomnia, bipolar Disorders, especially non-psychotic depressive disorder, and anxiety Disorders were reported [4]. Dissociative disorder is frequently observed alongside depressive Disorders [5]. In some individuals with dissociative amnesia, depressive symptoms can be seen together with self-harm, aggressive impulses, suicidal impulses and actions [6].…”
Section: Introductionmentioning
confidence: 99%
“…Current models of nightmare production seem to emphasize negative emotionality as having a central role in determining dream affects. Ağargün et al previously reported that the prevalence of childhood traumatic experiences was higher among adult who ''often'' had nightmares than among adults who ''sometimes'' or ''never'' had nightmares (Ağargün et al, 2003). With regard to the associations between nightmares and mental health status, Nielsen et al studied adolescents (aged 13-16) and reported a significant association between the frequency of nightmares and the level of anxiety (Nielsen et al, 2006).…”
Section: Nightmare; Etiologymentioning
confidence: 99%